Analisis Pembelajaran Berdiferensiasi Dalam Kurikulum Merdeka di SD Kristen 1 Waimahu - Glodia Leasa; Lisye Salamor; Ode Abdurrachman (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
The Merdeka Curriculum emphasizes student-centered learning through the implementation of differentiated instruction, an approach that accommodates the diversity of students’ readiness, interests, and learning profiles. However, preliminary observations in Grade III at SD Kristen 1 Waimahu revealed a heterogeneous classroom in which differentiated instruction was still minimally applied, as shown by materials, tasks, and media that had not been adjusted to each student’s ability. This study aims to analyze the implementation of differentiated instruction within the Merdeka Curriculum among Grade III students at SD Kristen 1 Waimahu. A descriptive qualitative approach was employed, involving the classroom teacher and 31 Grade III students as subjects, with data collected through interviews, observation, and documentation, then analyzed using the Miles and Huberman interactive model. The findings show that the teacher applied three differentiation strategies: process differentiation through guiding questions and diagnostic assessment, content differentiation through tiered worksheets adjusted to learning readiness, and product differentiation by allowing students to choose the form of their output, such as posters. The planning, implementation, and evaluation of differentiated instruction were carried out systematically and flexibly, thereby enhancing student engagement, motivation, and comprehension. These findings confirm that differentiated instruction can be implemented effectively at the elementary level when teachers carefully and consistently map students’ learning needs.